Scrap tire ashes in portland cement production - Trezza, Mónica Adriana (2009)
Scrap tires are not considered harmful waste, but their stocking and disposal are a potential health and environmental risk. Properly controlled calcinations at high temperatures make tire combustion an interesting alternative due to its high calorific power, comparable to that of fuel-oil. Consequently, using them as an alternative combustible material in cement kilns makes it possible to give it a valuable use. However, it remains to be assured whether the impurities added to the clinker through these fuels do not affect its structure or properties.This paper shows the studies carried out on different clinkers under laboratory conditions with different levels of addition of scrap tire ashes, added by partially replacing traditional fuel in cement kilns.